Molecular modelling of S1 and S2 subunits of SARS coronavirus spike glycoprotein - Spiga, Ottavia (Biochem Biophys Res Commun, 2003)
The S1 and S2 subunits of the spike glycoprotein of the coronavirus which is responsible for the severe acute respiratory syndrome (SARS) have been modelled, even though the corresponding amino acid sequences were not suitable for tertiary structure predictions with conventional homology and/or threading procedures. An indirect search for a protein structure to be used as a template for 3D modelling has been performed on the basis of the genomic organisation similarity generally exhibited by coronaviruses. The crystal structure of Clostridium botulinum neurotoxin B appeared to be structurally adaptable to human and canine coronavirus spike protein sequences and it was successfully used to model the two subunits of SARS coronavirus spike glycoprotein. The overall shape and the surface hydrophobicity of the two subunits in the obtained models suggest the localisation of the most relevant regions for their activity.